MindPlay online reading professional development: Enhancing teachers' skills for inclusive education - Abu-Hamour, Bashir; Al Hmouz, Hanan (Journal of Education and e-Learning Research, 2026)
Reading difficulties (RDs) present significant challenges for inclusive education, underscoring the need for professional development programs that equip teachers with evidence-based literacy instruction strategies. This study examined the effectiveness of the MindPlay Comprehensive Reading Course for Educators, an online professional development program combined with in-person training and coaching, used to enhance the knowledge and instructional skills of 48 in-service early childhood teachers in the United Arab Emirates working in inclusive classrooms. Using a mixed-methods design, the intervention included ten asynchronous online modules, a two-day face-to-face workshop, and ongoing coaching support. Quantitative findings revealed substantial gains in participants’ reading-related knowledge, with post-intervention scores more than doubling pre-intervention scores across key domains, including phonological awareness, phonics, fluency, grammar, vocabulary, and reading comprehension. Results from the comprehensive reading test demonstrated statistically significant improvement with a large effect size, indicating a strong program impact. Qualitative findings indicated high participant satisfaction, highlighting the program’s practical applicability, flexibility, and alignment with evidence-based reading instruction. Participants reported increased confidence in implementing explicit, structured literacy strategies in inclusive classrooms while recommending extended training time and practicum-based experiences. Overall, the findings support blended professional development as an effective and scalable model for strengthening teacher competencies and advancing inclusive literacy practices.